(untitled) (The Conference Hub, 2025)
According to medical statistics, data from the World Health Organization (WHO), allergic rhinitis (AR) affects up to 30% of the world’s population. In recent years, the prevalence of allergic nosologies has increased significantly, which is an acute socially significant problem, causing discomfort (swelling and itching of the eyes, nasal congestion and runny nose, difficulty breathing, periodic headaches), changes in appearance and decreased self-esteem, decreased productivity of workers. There are studies confirming that autoimmune diseases and bronchial asthma can develop against the background of chronic AR.